Sulfolobus Mutants, Generated via PCR Products, Which Lack Putative Enzymes of UV Photoproduct Repair. (7th July 2011) - Sakofsky, Cynthia J.; Runck, Laura A.; Grogan, Dennis W.
Abstract : In order to determine the biological relevance of two S. acidocaldarius proteins to the repair of UV photoproducts, the corresponding genes (Saci_1227 and Saci_1096) were disrupted, and the phenotypes of the resulting mutants were examined by various genetic assays. The disruption used integration by homologous recombination of a functional but heterologous pyrE gene, promoted by short sequences attached to both ends via PCR. The phenotypic analyses of the disruptants confirmed that ORF Saci_1227 encodes a DNA photolyase which functions in vivo, but they could not implicate ORF Saci_1096 in repair of UV- or other externally induced DNA damage despite its similarity to genes encoding UV damage endonucleases. The success of the gene-disruption strategy, which used 5 ′ extensions of PCR primers to target cassette integration, suggests potential advantages for routine construction of Sulfolobus strains.